ON THE NATURAL FREQUENCIES,COMPLEX MODE FUNCTIONS,AND CRITICAL SPEEDS OF AXIALLY TRAVELING LAMINATED BEAMS：PARAMETRIC STUDY - Ghayesh, Mergen H. (Acta mechanica solida Sinica, 2011)
The dynamic response of an axially traveling laminated composite beam is investigated analytically,with special consideration to natural frequencies,complex mode functions and critical speeds of the system.The equation of motion for a symmetrically laminated system,which is in the form of a continuous gyroscopic system,is considered;the equation of motion is not discretized — no spatial mode function is assumed.This leads to analytical expressions for the complex mode functions and critical speeds.A parametric study has been conducted in order to highlight the effects of system parameters on the above-mentioned vibration characteristics of the system.